An Experimental Study of Seepage Properties in Crushed Sandstone and Mudstone - Qi-Le Ding; Shuai-Bing Song (Advances in Civil Engineering)
To study the effects of compression rate and weight ratio of sandstone to mudstone on permeability, water flow tests were performed on crushed rocks using an in-house designed and built water flow apparatus. Seepage properties of sandstone and mudstone were tested on specimens under six axial displacement levels. The weight ratios of the six specimens of sandstone to mudstone were set to 1 : 0, 4 : 1, 3 : 2, 2 : 3, 1 : 4, and 0 : 1. A non-Darcy law was adopted to calculate the permeability in the experiments based on verification of the Reynolds number. Non-Darcy flow is found to be most significant when the axial displacement or mudstone content increases. The permeability in the experiments is found to be in the range of 9.1 × 10−15–9.492 × 10−13 m2, which is calculated from a quadratic polynomial fit between the flow velocity and pressure gradient. A compression rate of 28.6% and weight ratio of sandstone to mudstone of 60% are found to be key values affecting permeability. When the axial displacement of specimen A (1 : 0) increases from 10 mm to 30 mm, the compression rate (ratio of axial displacement to original specimen height) increases from 9.5% to 28.6%, and the permeability decreases by 83.8% to 1.534 × 10−13 m2. When the axial displacement is 10 mm and the content of mudstone is increased from 0% to 60%, the permeability decreases by 77.1% to 2.172 × 10−13 m2.